Pemberdayaan Ekonomi Masyarakat Melalui Open Booth UMKM RW 8 Kelurahan Rungkut Tengah - Ervia Okta Izzatul M; Annisa Lailatul B; Noor Rizkiyah (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The increasing demand for living necessities has become a polemic for Indonesian people at this time, the need for clothing and food has increased while income has decreased, the difficulty of getting a job has become a trigger for household inequality in Indonesia. Micro, Small and Medium Enterprises (MSMEs) are a strong mainstay to support the current economy, with products that vary in the processed sector, wet food, healthy drinks, and handicrafts that people can rely on. MSMEs RW 08, Rungkut Tengah Village, assisted by group 90 KKN-T students, MBKM, East Java "Veteran" Development University, seeks to empower the community's economy through MSME open booth activities in which there are sales of healthy food and beverage products, MSME branding, and effective marketing. modern. Thus it is hoped that it can help the economy of MSME players in RW 08, Rungkut Tengah Village, Surabaya.